Anti-infective Properties of the Golden Spice Curcumin - Praditya, Dimas; Kirchhoff, Lisa; Brüning, Janina; Rachmawati, Heni; Steinmann, Joerg; Steinmann, Eike (Frontiers in Microbiology, 2019)
The search for novel anti-infectives is one of the most important challenges in natural product research, as diseases caused by bacteria, viruses and fungi are influencing the human society all over the world. Natural compounds are a continuing source of novel anti-infectives drugs. Accordingly, curcumin, has been used for centuries in Asian traditional medicine to treat various disorders. Numerous studies have shown that curcumin possesses a wide spectrum of biological and pharmacological properties, acting e.g. anti-inflammatory, anti-angiogenic and anti-neoplastic, while no toxicity is associated with the compound. Recently, curcumin´s antiviral and antibacterial activity was investigated, and it was shown to act against various important human pathogens like influenza virus, hepatitis C virus, HIV and strains of Staphylococcus, Streptococcus and Pseudomonas. Despite the potency, curcumin has not yet been approved as a therapeutic antiviral agent. This review summarizes the current knowledge and future perspectives of the antiviral, antibacterial and antifungal effects of curcumin.